LO63: Humanoid robot-based distraction to reduce pain and distress during venipuncture in the pediatric emergency department: A randomized controlled trial. (May 2019) - Ali, S.; Manaloor, R.; Ma, K.; Sivakumar, M.; Vandermeer, B.; Beran, T.; Scott, S.; Graham, T.; Curtis, S.; Jou, H.; Beirnes, N.; Hartling, L.
Abstract : Introduction : Intravenous insertion (IVI) is identified by children as extremely painful and the resultant distress can have lasting negative consequences. There is an urgent need to effectively manage such procedures. Our primary objective was to compare the pain and distress of IVI with the addition of humanoid robot-based distraction to standard care, versus standard care alone.Methods : This two-armed randomized controlled trial (RCT) was conducted from April 2017 to May 2018 at the Stollery Children's Hospital emergency department (ED). Children aged 6 to 11 years who required IVI were included. Exclusion criteria included hearing or visual impairments, neurocognitive delays, sensory impairment to pain, previous enrolment, and discretion of the ED clinical staff. Primary outcomes were measured using the Observational Scale of Behavioural Distress-Revised (OSBD-R) (distress) and the Faces Pain Scale-Revised (FPS-R) (pain). A total of 426 pediatric patients were screened and 340 were excluded.Results : We recruited 86 children, of which 55% (47/86) were male; 9% (7/82) were premature at birth; 82% (67/82) had a previous ED visit; 30% (25/82) required previous hospitalization; 78% (64/82) had previous IV placement and 96% (78/81) received topical anesthesia. The mean total OSBD-R score was 1.49 ± 2.36 (standard care) compared to 0.78 ± 1.32 (robot group) (p = 0.047). The median FPS-R during the IV procedure was 4 (IQR 2, 6) in the standard care group alone, compared to 2 (IQR 0, 4) with the addition of humanoid robot-based distraction (p = 0.10). Change in parental state anxiety pre-procedure versus post-procedure was not significantly different between groups (p = 0.49). Parental satisfaction with the IV start was 93% (39/42) in the robot arm compared to 74% (29/39) in the standard care arm (p = 0.03). Parents were also more satisfied with management of their child's pain in the robot group (95% very satisfied) compared with standard care (72% very satisfied) (p = 0.002).Conclusion : A statistically significant reduction in distress was observed with the addition of robot-based distraction to standard care. Humanoid robot-based distraction therapy reduces distress and to a lesser extent, pain, in children undergoing IVI in the ED. Further trials are required to confirm utility in other age groups and settings.